KAJIAN KONDISI EKSISTING RENCANA PENINGKATAN JALAN STRATEGIS KABUPATEN SIKKA - Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
The unfavorable natural conditions in Sikka Regency are one of the main causes of limited access to parts of Sikka Regency, which are sometimes very difficult to reach by ordinary four-wheeled vehicles when the rainy season arrives. This research was carried out at 3 observation locations with 25 sample points in December 2021, at the first location there are 2 observation points, where points 1 and 2 are located in Gera Village, Mego District, Sikka Regency, according to field observations, both points are not included into a protected forest area. The types of plants/vegetation that dominate at that location are Candlenut tree (Aleurites moluccana (L.) Wild), white teak (Gmelina arborea), Cotton tree (Bombax ceiba L), Bamboo (Bambusa Sp) and understorey plants Kaliandra ( Calliandra calothyrsus). In the second location, there are 7 observation points, which are located in E'o Village, Hewokloang District, Sikka Regency. According to field observations, the existing road is in the form of concrete cement and some roads have been asphalted. The sample locations were dominated by woody plants such as White Teak (Gmelina arborea), Mahogany (Swetenia machrophylla), Tamarind (Tamarindus indica) and Mango (Mangifera indica). At the third location, there are 16 observation points, which are located in Egon Village, Wairbleler Village and Nagatobong Village, Waigete District, Sikka Regency. At the observation site, plant species were dominated by woody plants/mixed jungle trees, multy purpose tree species and plantation crops including Ampupu (Eucalyptus urophylla), Banyan (Ficus benjamina), Red Wood (Pterocarpus indicus), December tree (Erytrina subumbrans), Bamboo (Bambusa Sp. ), Avocado (Persea americana), White Teak (Gmelina Arborea) Candlenut (Aleurites moluccana), Mahogany (Swetenia machrophylla), Coconut (Cocos nucifera), Cotton tree (Ceyba petandra), Chocolate (Theobroma cacao L), Cashew (Anacardium occidentale), and understorey plants Kaliandra (Calliandra calothyrsus). The plan to improve the strategic road of Sikka Regency, according to field observations, will not have an impact on forest destruction or tree cutting. This is because the existing condition of the road at the location of the planned road improvement is already an existing road, that will only be improved in the form of hotmix and cement concrete in several segments that have not been done before.